Performance Evaluation of Constructed Wetlands for Domestic Wastewater Treatment - Hakim, Muhammad Irfan; Rahman, Siti Nur Aisyah (RESWARA: Jurnal Riset Ilmu Teknik, 2025)
Constructed wetlands (CWs) have emerged as an environmentally sustainable and cost-effective technology for domestic wastewater treatment, particularly in developing and tropical regions. This study aims to evaluate the performance of various constructed wetland configurations for domestic wastewater treatment based on a systematic synthesis of recent empirical studies. The research employed a structured literature analysis of peer-reviewed journal articles published between 2021 and 2025, focusing on pollutant removal efficiencies, system configurations, vegetation types, and operational conditions. The results indicate that constructed wetlands consistently achieve high removal efficiencies for organic matter and suspended solids, with reported reductions ranging from 70% to 95% for biochemical oxygen demand (BOD), 60% to 90% for chemical oxygen demand (COD), and 75% to 98% for total suspended solids (TSS). Vertical flow and hybrid constructed wetlands generally outperform horizontal subsurface flow systems, particularly in nitrogen and phosphorus removal. The integration of innovative elements such as biochar media, aeration, and microbial fuel cells further enhances treatment performance and pollutant degradation. This study confirms that constructed wetlands are a robust and adaptable solution for domestic wastewater treatment, offering significant environmental and socio-economic benefits. The findings support the wider implementation of constructed wetlands as a decentralized wastewater treatment strategy and highlight the importance of optimizing design parameters and plant selection for site-specific conditions.